2011
DOI: 10.1007/s12029-011-9269-x
|View full text |Cite
|
Sign up to set email alerts
|

ZIP14 Zinc Transporter Downregulation and Zinc Depletion in the Development and Progression of Hepatocellular Cancer

Abstract: Purpose Hepatocellular cancer (HCC) is a deadly and most rapidly increasing cancer in the USA and worldwide. The etiology and factors involved in development of HCC remain largely unknown. A marked decrease in zinc occurs in HCC. Its role and involvement in HCC has not been identified. We investigated the relationship of cellular zinc changes to the development of malignancy, and the identification of potential zinc transporters associated with the inability of hepatoma cells to accumulate zinc. Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 23 publications
(18 reference statements)
8
53
0
Order By: Relevance
“…Only one study (Ebara et al 13 ) had reported a zinc increase in HCC, which was subsequently reversed by pursuant studies of the Ebara group 5,6 that showed a consistent significant decrease in zinc in HCC. In addition, our studies 14 with tissue samples from 26 HCC cases identifies the specific zinc decrease in the hepatoma cells in well-differentiated and advancing malignancy, as compared to the higher zinc in the normal hepatocytes (Fig. 2).…”
Section: The Status Of Zinc Levels In Hccmentioning
confidence: 67%
See 3 more Smart Citations
“…Only one study (Ebara et al 13 ) had reported a zinc increase in HCC, which was subsequently reversed by pursuant studies of the Ebara group 5,6 that showed a consistent significant decrease in zinc in HCC. In addition, our studies 14 with tissue samples from 26 HCC cases identifies the specific zinc decrease in the hepatoma cells in well-differentiated and advancing malignancy, as compared to the higher zinc in the normal hepatocytes (Fig. 2).…”
Section: The Status Of Zinc Levels In Hccmentioning
confidence: 67%
“…With this brief background, the issue of zinc treatment for HCC can be addressed. The commonly employed HepG2 cell line exhibits ZIP14 expression with evidence of the transporter localization at the plasma membrane, 14 which is in contrast to the HCC in situ silencing of ZIP14 expression and absence of transporter localization at the plasma membrane shown in Figure 3. This is an important relationship that must be recognized and addressed in any experimental studies of the potential efficacy of a zinc treatment approach for HCC.…”
Section: Zinc For the Treatment/prevention Of Hccmentioning
confidence: 88%
See 2 more Smart Citations
“…Such a relationship exists for zinc and ZIP1 in prostate cancer. [32][33][34] These are potential biomarkers for the early developing premalignant stages of pancreatic carcinogenesis.…”
Section: Methodsmentioning
confidence: 99%